2000
DOI: 10.1001/archopht.118.2.257
|View full text |Cite
|
Sign up to set email alerts
|

Anterior Chamber Depth Measurement as a Screening Tool for Primary Angle-closure Glaucoma in an East Asian Population

Abstract: Setting: Rural and urban locations in the Hö vsgö l and Ö mnö gobi provinces, Mongolia. Participants: Nine hundred forty-two (94.2%) of 1000 individuals in Hö vsgö l (1995) and 775 (96.9%) of 1000 individuals in Ö mnö gobi (1997) aged 40 years or older were examined. Main Outcome Measures: Anterior chamber depth was measured by optical pachymetry, slitlamp-mounted Amode ultrasound, and handheld ultrasound. Gonioscopy was used to detect occludable angles, defined as one in which the trabecular meshwork was visi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
113
0
3

Year Published

2000
2000
2015
2015

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 163 publications
(119 citation statements)
references
References 19 publications
(10 reference statements)
3
113
0
3
Order By: Relevance
“…[35][36][37][38] A small anterior segment represents a major risk factor with limbal and axial anterior chamber depth being the traits most strongly correlated with ACG. [39][40][41] In eyes with hyperopia or shallow anterior chamber depth, the iris is repositioned so that its anterior movement during dilation blocks the iridocorneal angle. This can lead to an acute entrapment of aqueous fluid behind the iris and a rapid increase in IOP.…”
Section: Pacg Risk Factorsmentioning
confidence: 99%
“…[35][36][37][38] A small anterior segment represents a major risk factor with limbal and axial anterior chamber depth being the traits most strongly correlated with ACG. [39][40][41] In eyes with hyperopia or shallow anterior chamber depth, the iris is repositioned so that its anterior movement during dilation blocks the iridocorneal angle. This can lead to an acute entrapment of aqueous fluid behind the iris and a rapid increase in IOP.…”
Section: Pacg Risk Factorsmentioning
confidence: 99%
“…5 On the other hand, Congdon et al 7 reported that peripheral slit beam tests such as that of van Herick do not correlate with findings obtained using a gonioscope as well as ultrasonic examination. Judging from the results obtained in this study and those of previous reports, however, van Herick's method is considered to be effective as a screening method for glaucoma patients.…”
Section: Discussionmentioning
confidence: 98%
“…6,8,9 However, there are divergent opinions regarding the usefulness of peripheral anterior chamber depth measurement, 1,7 and there have also been reports indicating the usefulness of central anterior chamber depth measurement. 5 Consequently, a definite conclusion has yet to be reached concerning the usefulness of peripheral anterior chamber depth measurement. There are also few reports describing the usefulness of peripheral anterior chamber depth measurement in Japanese.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…13,[17][18][19][20][21] Devereux et al 18 reported a sensitivity of 77% and a specificity of 83% in a study that used a slitlamp mounted ultrasound ACD measurement system. Congdon et al 17 reported a sensitivity of 88% and a specificity of 92% using ultrasonography in combination with tonography.…”
Section: Discussionmentioning
confidence: 99%